One-pot synthesis of a CaBi2O4/graphene hybrid aerogel as a high-efficiency visible-light-driven photocatalyst. (March 2023) - Lv, Tiantian; Zhao, Yan; Li, Sai; Zhang, Lei; Wu, Fan; Liu, Zongxing; Yu, Chunna; Zhao, Chang; Xing, Guangjian
Abstract: At present, the development of broad-spectrum and visible-light-driven photocatalysts is highly desirable for sewage treatment, which is due to the serious environmental pollution in the world. A CaBi2 O4 /graphene aerogel (CaBi2 O4 /GA), as a high-efficiency photocatalyst, has in the present study been successfully prepared using a one-pot hydrothermal method combined with a freeze-drying process. The as-prepared CaBi2 O4 /GA composite exhibited a macroporous three-dimensional (3D) network structure with lamellar CaBi2 O4 particles distributed on the graphene sheets. Considering the wide range of visible-light absorption and a suitable band gap, CaBi2 O4 /GA has here been explored as a plausible photocatalyst for the degradation of several dyes and antibiotic drugs. Under visible light irradiation for 120 min, the photodegradation efficiencies were found to be 93.37%, 87.16%, 91.69%, and 93.25% for methyl orange, rhodamine B, methylene blue, and tetracycline hydrochloride, respectively. For dye/drug wastewater solutions under real sunlight irradiation, CaBi2 O4 /GA showed a high degradation efficiency. In fact, CaBi2 O4 /GA exhibited an improved photodegradation activity compared to pure CaBi2 O4 and CaBi2 O4 /graphene. Based on the measurements of photoluminescence spectra and electrochemical impedance spectra, the photocatalytic mechanism of CaBi2 O4 /GA was proposed to clarify its photodegradation process. Trapping tests indicated that the ·O2 − radicals played a key role in the photocatalytic reaction as a dominant reactive species. The advantage of a macroporous 3D structure, suitable band gap, high photodegradation efficiency, and cyclic stability promotes the practical applications of CaBi2 O4 /GA as a high-efficiency visible-light-driven photocatalyst in wastewater treatment. Graphical abstract: Image 1 Highlights: CaBi2 O4 /graphene aerogel (CaBi2 O4 /GA) was prepared using one-pot hydrothermal method. CaBi2 O4 /GA shows high efficiency for degrading dye/drug under visible light/sunlight. CaBi2 O4 /GA exhibits superior cycling stability for photodegradation of dye/drug.